2012
DOI: 10.1007/s11999-011-2045-1
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Cruciate Ligament and Posterolateral Corner Deficiency Results in a Reverse Pivot Shift

Abstract: Background As measured via static stability tests, the PCL is the dominant restraint to posterior tibial translation while the posterolateral corner is the dominant restraint to external tibial rotation. However, these uniplanar static tests may not predict multiplanar instability. The reverse pivot shift is a dynamic examination maneuver that may identify complex knee instability. Questions/purposes In this cadaver study, we asked whether (1) isolated sectioning or (2) combined sectioning of the PCL and poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…12 In a recent cadaveric experiment, our group utilized computer-assisted navigation to describe the effects of serial sectioning of the PCL and PLC structures on the magnitude of a mechanized RPS. 19 We demonstrated that combined sectioning of both the PCL and PLC structures was necessary to elicit a significant increase in magnitude of the RPS. Consequently, for the purposes of this study, we chose to section the PCL and PLC structures to induce a mechanized RPS and determine if alterations in tibial slope could influence the magnitude of this dynamic test.…”
Section: Petrigliano Et Almentioning
confidence: 77%
See 2 more Smart Citations
“…12 In a recent cadaveric experiment, our group utilized computer-assisted navigation to describe the effects of serial sectioning of the PCL and PLC structures on the magnitude of a mechanized RPS. 19 We demonstrated that combined sectioning of both the PCL and PLC structures was necessary to elicit a significant increase in magnitude of the RPS. Consequently, for the purposes of this study, we chose to section the PCL and PLC structures to induce a mechanized RPS and determine if alterations in tibial slope could influence the magnitude of this dynamic test.…”
Section: Petrigliano Et Almentioning
confidence: 77%
“…14 Our laboratory has developed a mechanized pivot-shift device, which in combination with computer navigation can be used to quantify translations of the tibia relative to the femur during the pivot-shift and RPS maneuver. 16,19 In a previous cadaveric study, we demonstrated that the combined sectioning of both the PCL and the structures of the PLC was necessary to generate a significant increase in the magnitude of the RPS relative to the intact state. 19 Furthermore, the magnitude of the RPS appeared to demonstrate a strong correlation to the magnitude of the posterior drawer and external rotation tests.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…There are many ways in which this test has been reproduced with the main focus on increased external rotation on the injured side as the key measure of potential PLC injury. Pearle and others have abandoned the use of rotation alone and have incorporated lateral compartment translation as the key measure [ 12 , 25 ]. The use of the electromagnetic tracking system during the dial test allows for a measure of proximal tibial translation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, isolated increased external tibial axial rotation may not identify the patient with a PLC injury without additional manoeuvres during the examination [ 13 , 14 ]. A description of rotatory instability by measuring the relative translation of the lateral compartment of the knee with respect to the medial compartment appears to provide better accuracy in the diagnosis of a PLC injury [ 7 , 25 ].…”
Section: Introductionmentioning
confidence: 99%